PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERINTEGRASI PEMBELAJARAN SOSIAL EMOSIONAL UNTUK MENINGKATKAN MINAT BELAJAR DAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Prasetya, Ahmad Dika; Sutarto; Sabrun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve students' learning interest and mathematical communication skills through the implementation of the Jigsaw cooperative learning model integrated with Social Emotional Learning (SEL). The study was conducted in two cycles involving Grade VIII students of SMP Negeri Satu Atap 1 Keruak in the 2025/2026 academic year. Each cycle consisted of planning, action, observation, and reflection stages. Data were collected through learning interest questionnaires, mathematical communication skills tests, observation sheets of student activities, and observation sheets of teacher activities. The results showed a significant improvement in students' learning interest and mathematical communication skills after the implementation of the Jigsaw cooperative learning model integrated with SEL. Students' learning interest increased from 28.3% in the pre-cycle stage to 69.23% in Cycle I and reached 86.8% in Cycle II. Meanwhile, students' mathematical communication skills improved from an average score of 25.8 in the pre-cycle stage to 57.4 in Cycle I and 80.6 in Cycle II, with classical mastery reaching 80.65%. These findings indicate that the implementation of the Jigsaw cooperative learning model integrated with Social Emotional Learning is effective in enhancing students' learning interest and mathematical communication skills in mathematics learning.